Desenvolvimento e validação de questionário para acompanhamento dos egressos da Pós-Graduação Stricto Sensu - Silva, Sandra da [UNIFESP] (2019)
Introduction: The Higher Education Personnel Improvement Coordination (CAPES) recommends and encourages the Post-Graduation Programs (PGP) to follow upex-students, focusing on improvement and new strategies of the respective Programs. Objective: To develop and validate a questionnaire to follow up ex-students of Post-Graduation Stricto Sensu. Method: The databases MEDLINE, LILACS, SciELO Virtual Library and Google Scholar websites were used to search the subject of study. A questionnaire with open and closed questions was developed from the researched literature and according to Design Thinking methodology. The questionnaire was structured via Google Forms and sent to all ex-students of Post-Graduation Program in Translational Surgery at UNIFESP (PPG-CT) (January 2001 to December 2017) and to ex-students of Professional Master in Science, Technology and Management Applied to Tissue Regeneration course of UNIFESP-EPM (MP-RT) (January 2015 to December 2017). Five permanent professors, from PPG-CT and MP-RT, participated in Empathy phase attending to the needs, gaps and difficulties of ex-students´ theme, and developed the permanent professors´ questionnaire (PPQ). This questionnaire was answered by six other permanent professors and served as the basis for the development of the questionnaire sent to ex-students (Experimentation phase). Results: The ex-students did not present difficulties to the questionnaire answers. The response rate was 56.1% (N = 146) for ex-students from PPG-CT and 76.2% (N = 16) for MP-RT. There was a predominance of women (30.8%) in PPG-CT (M), aged 36-50 years (37.0%), graduated from private institutions (28.8%) and currently employed (30, 1%). In PPG-CT (D), the predominance was men (24.0%) over 51 years of age (20.5%), graduated from public institutions (26.7%) and currently employed (27 , 4%).In PPG-CT (PD), the predominance was men (2.7%), over 51 years of age (4.1%), graduated from public institutions (3.4%) and currently employed (4 ,1%). There was an equal proportion between men and women (50.0%) for ex-students of MP-RT, the age groups of 20-35 years and 36-50 years were of equal proportion (43.7%), graduated from public institutions (56.2%) and currently employed (56.2%). Conclusion: A questionnaire was developed and validated to follow up the ex-students of Post-Graduation Program Stricto Sensu.